Donkey milk as a traditional remedy in the Andean community of Peru - Gutiérrez-Gómez, Edgar; Ñaupa-Figueroa, José Luis; González-Ríos, Rosa Cecilia; Aspur-Barritos, Jaime Carmelo; Quispe-Rodríguez, Juan; Ccama-Uchiri, Faustino (Frontiers in Sustainable Food Systems, 2025)
Donkey milk was ancestrally used in the Andean communities of Peru as a natural remedy to treat various ailments, including asthma, gastritis and bronchitis. This qualitative ethnographic research explores the traditional knowledge associated with its use, therapeutic value and marketing practices in rural and urban contexts. In-depth interviews, participant observation and focus groups with producers, vendors and consumers in the city of Ayacucho and surrounding communities were used. The results show that donkey milk is considered an alternative to conventional medicine and, in some cases, a substitute for breast milk. However, its sale is informal, without sanitary regulation, and loaded with cultural stigmas. Information is transmitted orally, mainly in Quechua, which limits its scientific systematization. It is concluded that it is urgent to revalue this ancestral knowledge and integrate it into intercultural health and food security policies.